Design of Miniaturized Dual-Band Wilkinson Power Divider Using Dual and Cascade Pi-Shaped Transmission Lines - M. Kumar; S. K. Parui; S. Das (Radioengineering, 2018)
This paper presents a design of compact dual-band Wilkinson power divider (WPD). The cascaded pi-shape and dual transmission lines are used instead of conventional transmission line sections of the reference WPD in order to miniaturize the circuit area. Therefore, 62% size reduction has been achieved without much affecting the performance of power divider. The insertion-loss of the output ports is within (3.4±0.3)dB, for the reflection coefficient is better than -15 dB and isolation is better than 18 dB at the lower frequency band of 1.1 GHz. Similarly the insertion loss is within (3.4±0.3) dB, for the reflection coefficient better than -18 dB and isolation better than at the upper frequency band of 2.55 GHz. The proposed WPD is analyzed, fabricated and tested. It is found that the measurement results are in good agreement with the simulated one.